Minor Neurological Dysfunction: A Comparative Study in Pediatrics with Different Types of Focal Epilepsy - Cam, Yagmur; Tekin-Orgun, Leman; Soysal-Acar, A. Sebnem; Gucuyener, Kivilcim; Elbasan, Bulent (Journal of Pediatric Epilepsy, 2024)
Epilepsy is a disorder that occurs as a result of abnormal neuronal discharges in the brain and affects approximately 1% of children. Sensorimotor function impairments that are related to minor neurological deficits may be seen even in children diagnosed with epilepsy solely. This study aims to determine the type and areas of minor neurological dysfunction (MND) in children with Self-Limited Focal Epilepsy (SeLFE) and to compare the children with Self-Limited Epilepsy with Centrotemporal Spikes (SeLECTS) and SeLFE without SeLECTS. Fifty-six children diagnosed with epilepsy (28 SeLECTS and 28 SeLFE without SeLECTS) were included in the study. Both groups consisted of 13 girls and 15 boys. The mean ages of SeLECTS and SeLFE without SeLECTS groups were 9.68 ± 1.63 and 9.32 ± 1.62, respectively. A Modified Touwen Neurological Examination was performed to determine the type and areas of MND. There were no differences between the groups regarding MND type, coordination, fine manipulation, sensory, and involuntary movement areas (p > 0.05). It should be considered that children with SeLECTS may be neurologically affected as much as children with other types of epilepsy. Long-term problems due to epilepsy may be minimized by short-term neurodevelopmental follow-ups.
Keywords: fine motor skills; pediatric epilepsy; rolandic epilepsy; sensorimotor; Touwen